Manufacturing process of glass fiber reinforced plastic cylinder

By using glass fiber mesh cloth, flame retardant powder and fillers in the preparation process of fiberglass cylinders, and using vacuum casting and high-temperature curing processes, the problems of insufficient flame retardant performance and mechanical properties of the existing fiberglass cylinders are solved, achieving higher performance and lower costs.

CN119773270AActive Publication Date: 2025-04-08SHANGHAI TANGSHENG ENVIRONMENTAL PROTECTION TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510295802.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-13
Publication Date
2025-04-08
Estimated Expiration
2045-03-13

AI Technical Summary

Technical Problem

When used in MR equipment, the flame retardant performance and mechanical properties are insufficient, making it difficult to meet the high performance requirements.

Method used

A glass fiber mesh cloth is used as the mold surface, and flame retardant powder and filler are added. Through vacuum casting and high-temperature curing processes, the flame retardant capacity and mechanical properties of the product are improved.

Benefits of technology

It significantly improves the flame retardant performance and mechanical properties of the fiberglass cylinder, reduces production costs, improves production capacity efficiency, and ensures the safety and reliability of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119773270A_ABST
    Figure CN119773270A_ABST
Patent Text Reader

Abstract

The invention relates to a manufacturing process of a glass fiber reinforced plastic cylinder and belongs to the technical field of glass fiber reinforced plastic preparation. Comprising the following preparation steps: S1, cleaning and demolding treatment; s2, glass fiber gridding cloth is laid, and mold closing is conducted; s3, mold preheating; s4, preparing a sizing material; s5, vacuum pouring is conducted; s6, curing and demolding; and S7, carrying out post-treatment. According to the process, the glass fiber mesh cloth is used, meshes in the mesh cloth can facilitate flowing of a sizing material, flame-retardant powder is added into the sizing material, the flame-retardant capacity of the product can be improved, the filler can prevent implosion and cracks of the product, and meanwhile the product cost can be reduced; the compactness is increased through vacuum pouring, and then the mechanical performance of the product is improved through high-temperature curing. The process can reduce the cost and improve the productivity efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of glass fiber reinforced plastic preparation, and relates to a manufacturing process of a glass fiber reinforced plastic cylinder. Background Art

[0002] In medical devices, especially in MR (magnetic resonance) equipment, the transmitting coil cylinder plays a vital role. FRP is a composite material made of resin and glass fiber and other reinforcing materials through a composite process. Due to its advantages of light weight, high strength, corrosion resistance, good insulation and strong designability, FRP has been widely used in the field of medical devices. Therefore, FRP, as an advanced composite material, is widely used in the manufacture of these transmitting coil cylinders due to its unique properties.

[0003] With the continuous development and popularization of MR technology, the performance requirements for the transmitting coil cylinder are getting higher and higher. The flame-retardant fiberglass cylinder has an increasingly broad application prospect in MR equipment due to its excellent flame retardant properties, light weight and high strength, good mechanical properties and easy processing and molding. Fiberglass with good flame retardant properties can effectively prevent the spread of fire in extreme situations such as fire, protecting the safety of MRI equipment and patients.

[0004] Therefore, it is necessary to develop a preparation process for a FRP cylinder with excellent flame retardancy and mechanical properties. Summary of the invention

[0005] The purpose of the present invention is to provide a manufacturing process for a glass fiber reinforced plastic cylinder. In this process, glass fiber mesh cloth is used. The mesh on the mesh cloth can facilitate the flow of rubber. Flame retardant powder is added to the rubber to improve the flame retardant ability of the product. The filler can prevent the product from imploding and cracking, and can reduce the product cost. The density is increased by vacuum casting, and the mechanical properties of the product are improved by high temperature curing. This process can reduce costs and improve production efficiency.

[0006] The purpose of the present invention can be achieved through the following technical solutions: A process for manufacturing a glass fiber reinforced plastic cylinder comprises the following steps: S1. Cleaning and demoulding: Clean the mold with acetone, dry it at 60°C for 24 hours, and evenly apply a layer of polyethylene wax release agent on the dry mold surface; S2. Laying fiberglass mesh cloth and closing the mold: Lay the fiberglass mesh in the mold, roll it to remove air bubbles, and then put the mold together to ensure that all edges and gaps fit tightly; S3, mold preheating: After checking the air tightness, preheat the mold and keep it at 80~100℃ for 1~2h; S4. Rubber preparation: The epoxy resin was preheated at 80°C for 30 minutes, and then the epoxy resin: curing agent: flame retardant powder: filler with a mass ratio of (25-30): (25-30): (28-32): 15 was stirred in a stirring kettle at a speed of 1000 r / min for 30-50 minutes, and a rubber compound was prepared by vacuum degassing. S5. Vacuum casting: The vacuum degree in the mold is drawn to -0.85~-0.95MPa, and then the rubber material is introduced into the mold from the bottom, and poured from bottom to top until the rubber material fills the top outlet of the mold, and then the valve at the top outlet of the mold is closed, and the pressure of the mold filled with rubber material is increased to 0.6~0.7MPa, and the pressure increase rate is 0.1MPa / min, in which the valve is closed for 2min, opened for 30s, and the pressure is maintained for 10~15min; S6, curing and demoulding: The mold after step S5 is cured at high temperature, and after being completely cured, it is naturally cooled to room temperature, demoulding, and CNC trimming are performed to obtain the FRP cylinder A; S7, post-processing: The surface of the FRP cylinder A after step S6 is subjected to sandblasting and paint spraying treatment to obtain the FRP cylinder.

[0007] As a preferred technical solution of the present invention, in step S4, the preparation process of the filler is as follows: S2.1, quartz powder and aluminate coupling agent in a mass ratio of 30:1 were mixed, ball milled at a speed of 300 r / min for 3 h, and then passed through a 200 mesh sieve to obtain a mixture A, and then anhydrous ethanol 7 times the mass of the mixture A was added, stirred at a speed of 500 r / min for 1-2 h at 40-45 ° C, heated to 100-120 ° C, and dried for 12 h to obtain a mixture B; S2.2. A mixture of B, polyacrylamide and deionized water in a mass ratio of 10:1:25 is stirred at a constant speed for 1-2 hours to obtain a solid C after drying. The solid C is ground at a speed of 300 r / min for 3 hours and then passed through a 300-mesh sieve to obtain modified quartz powder.

[0008] As a preferred technical solution of the present invention, in step S4, the preparation process of the flame retardant powder is as follows: S3.1, in parts by weight, at room temperature, dispersing 10 to 15 parts of barium carbonate in 70 to 90 parts of deionized water to obtain a suspension A, dissolving 10 to 15 parts of phytic acid in 65 parts of deionized water to obtain a phytic acid solution, mixing the phytic acid solution with the suspension A and stirring at a speed of 300 to 400 r / min for 5 hours, filtering after the stirring, washing with deionized water, and drying the obtained solid to obtain a barium phytate solid; S3.2. Aluminum hydroxide and barium phytate solids in a mass ratio of (3-5):1 are stirred at a speed of 300-400 r / min for 20-30 min to obtain a mixture C, 20 parts of the mixture C are mixed with 20-25 parts of a lignin mixed solution, stirred at a speed of 300-400 r / min for 2-4 h, dried at 80-95°C for 15 h, and then ball-milled at a speed of 300 r / min for 1 h in a ball mill to obtain the flame retardant powder.

[0009] As a preferred technical solution of the present invention, in step S2, the glass fiber mesh is a twist-free woven reinforced mesh.

[0010] As a preferred technical solution of the present invention, in step S6, the process of curing at high temperature is: firstly raising the temperature to 100°C and keeping it for 2-3 hours, and then raising the temperature to 125°C and keeping it for 4-5 hours.

[0011] As a preferred technical solution of the present invention, in step S7, the sand used in the sandblasting treatment is quartz sand material with a particle size of 100 mesh and a treatment pressure of 5.0 MPa.

[0012] As a preferred technical solution of the present invention, in step S7, the paint is epoxy resin paint.

[0013] As a preferred technical solution of the present invention, in step S2.2, the drying condition is drying at 90° C. for 12 hours.

[0014] As a preferred technical solution of the present invention, in step S3.1, the drying condition is drying at 75-80°C for 12-17h.

[0015] As a preferred technical solution of the present invention, in step S3.2, the lignin mixed solution contains nano-lignin, ethanol and water in a mass ratio of 2:2:7.

[0016] The invention adds flame retardant powder into epoxy resin, which can improve the flame retardant ability of the product, and the filler can prevent the product from implosion and cracking, and can reduce the product cost at the same time.

[0017] During the preparation of flame retardant powder, barium phytate is prepared first and then mixed with aluminum hydroxide, so that phosphorus can be introduced into aluminum hydroxide. The phosphorus element in barium phytate can promote the formation of a carbon layer on the surface of the material during combustion, thereby preventing heat and oxygen from transferring to the interior of the material and reducing the generation of combustible gases. It complements the flame retardant mechanisms of aluminum hydroxide such as heat absorption and dilution, and enhances the overall flame retardant effect through a synergistic effect.

[0018] Furthermore, lignin is added continuously. Lignin is easy to form a carbon layer during the combustion process. Combined with the effect of barium phytate in promoting carbonization, the carbonization ability of the material is further enhanced. In addition, the lignin mixture can make aluminum hydroxide and barium phytate mix better together to form a uniform mixture. At the same time, it can also play a dispersing role, so that the components in the flame retardant powder are evenly distributed in the rubber material, avoiding the situation where the flame retardant powder concentration is too high or too low in the epoxy resin, and ensuring the performance stability of the flame retardant powder.

[0019] The flame retardant system composed of aluminum hydroxide and barium phytate tends to increase the brittleness of the material, resulting in cracking and breaking during the overall process of the rubber casting process or the use of the FRP cylinder. Lignin has certain flexibility and adhesion, so adding lignin to the flame retardant powder can also improve the toughness of the rubber, reduce the brittleness of the material, and increase durability.

[0020] The filler is obtained by treating quartz powder with aluminate coupling agent and polyacrylamide. The surface of quartz is usually inert. After being treated with aluminate coupling agent, new active functional groups can be introduced on the surface of quartz, thereby improving the surface activity of quartz, making it more compatible with the polarity of epoxy resin matrix, enhancing the interface affinity between quartz and resin, and improving the compatibility between the two.

[0021] At the same time, when the quartz particles treated with aluminate coupling agents are close to each other, the interaction between the molecular chains of the coupling agent prevents the agglomeration of the particles, allowing the quartz to be more evenly dispersed in the epoxy resin.

[0022] The polyacrylamide molecular chain contains a large number of polar groups, which can interact with the coupling agent or other active sites on the surface of the quartz powder in the mixture B, further improving the surface properties of the quartz powder. Polyacrylamide can form a polymer protective film on the surface of the quartz powder, and has good dispersing and thickening effects, which can make the quartz powder disperse better. Certain groups on the molecular chain of ammonium polyacrylate can chemically react or physically entangle with the polymer matrix, forming a bridge between the quartz powder and the polymer, so that the two can be better combined together, improving the overall performance of the composite material. In addition, the oil absorption value of quartz powder is high, which often requires more resin consumption, which will affect the production cost and the processing performance of the material. The oil absorption value of quartz powder can be reduced by modification, so that it can be more effectively mixed with epoxy resin when preparing composite materials, reducing the consumption of resin, reducing costs and improving processing performance.

[0023] Beneficial effects of the present invention: (1) In this process, the mold is first cleaned and demoulded to ensure that there is no oil or impurities. Then, a glass fiber mesh is laid. The mesh on the mesh is conducive to the flow of the rubber. The mold is preheated before the rubber is poured. The rubber is poured from bottom to top. During the rising filling process, the rubber can gradually squeeze the small amount of air remaining in the mold upward and discharge it from the top outlet, further ensuring that there are no defects such as bubbles and pores inside the product. Compared with pouring from top to bottom, introducing the rubber from the bottom allows the rubber to fill the mold cavity more smoothly, improves the integrity and uniformity of the filling, reduces turbulence and splashing of the rubber during the flow process, avoids local stress concentration or uneven distribution of the rubber caused by the impact of the rubber, and is conducive to improving the stability of product quality. In addition, since flame retardant powder is added to the rubber, the flame retardant ability of the product can be improved. The added filler can prevent the product from implosion and cracking, while reducing the product cost. At the same time, the pressure maintenance during the pouring process can reduce the voids in the product and increase the density.

[0024] (2) During the pouring process, the pressure increase rate is 0.1MPa / min. By slowly increasing the pressure, the rubber compound can have enough time to adapt to the pressure change in the mold, avoiding the rubber compound flowing too fast or generating turbulence due to the sudden increase in pressure, thereby ensuring the uniform distribution of the rubber compound in the mold. The valve is closed for 2 minutes and opened for 30 seconds to balance the pressure. Opening the valve can release the local excessive pressure in the mold caused by the curing of the rubber compound, making the pressure distribution in the mold more uniform, avoiding the local excessive pressure from damaging the mold or causing defects in the product, and then ensuring the full curing of the rubber compound, eliminating stress and improving quality by maintaining the pressure.

[0025] (3) Through high temperature curing and the use of two temperature stage temperature settings, the mechanical properties of the product can be improved. This process can reduce costs and improve production efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to facilitate understanding by those skilled in the art, the present invention is further described below with reference to the accompanying drawings.

[0027] Figure 1 This is the overall process flow chart of this process. DETAILED DESCRIPTION

[0028] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.

[0029] In the comparative examples and embodiments of the present invention: The glass fiber mesh used is a twistless woven reinforced mesh, model ENG260L-1130; the epoxy resin used is MERICAN 3221A; the curing agent used is MERICAN 3221B; quartz was purchased from Huachang Polymer Co., Ltd. of East China University of Science and Technology; aluminate coupling agent was purchased from Hubei Fangde New Materials Co., Ltd.; polyacrylamide was purchased from Shanghai Yuanye Biotechnology Co., Ltd.; aluminum hydroxide was purchased from Huachang Polymer Co., Ltd. of East China University of Science and Technology; lignin was purchased from Yigao Zhuoxin Energy Saving Technology (Shanghai) Co., Ltd.

[0030] Example 1 Preparation of filler: S2.1, quartz powder and aluminate coupling agent in a mass ratio of 30:1 were mixed, ball milled at a speed of 300 r / min for 3 h, and then passed through a 200 mesh sieve to obtain a mixture A, and then anhydrous ethanol 7 times the mass of the mixture A was added, stirred at a speed of 500 r / min for 1 h at 40°C, heated to 100°C and dried for 12 h to obtain a mixture B; S2.2. A mixture of B, polyacrylamide and deionized water in a mass ratio of 10:1:25 was stirred at a constant speed for 1 hour, and dried at 90°C for 12 hours to obtain solid C. Solid C was ground at a speed of 300 r / min for 3 hours and then passed through a 300-mesh sieve to obtain modified quartz powder.

[0031] Preparation of flame retardant powder: S3.1. In parts by weight, at room temperature, 10 parts of barium carbonate are dispersed in 70 parts of deionized water to obtain a suspension A, and 10 parts of phytic acid are dissolved in 65 parts of deionized water to obtain a phytic acid solution. The phytic acid solution and the suspension A are mixed and stirred at a speed of 300 r / min for 5 hours. After the stirring is completed, the mixture is filtered and washed with deionized water for 5 times. The obtained solid is dried at 75° C. for 12 hours to obtain a barium phytate solid. S3.2. Aluminum hydroxide and barium phytate solids in a mass ratio of 3:1 are stirred at a speed of 300 r / min for 20 minutes to obtain a mixture C, 20 parts of the mixture C are mixed with 20 parts of a lignin mixed liquid, wherein the lignin mixed liquid contains nano-lignin, ethanol and water in a mass ratio of 2:2:7, the mixture is stirred at a speed of 300 r / min for 2 hours, dried at 80°C for 15 hours, and then ball-milled in a ball mill at a speed of 300 r / min for 1 hour to obtain the flame retardant powder.

[0032] Preparation of FRP cylinder: S1. Cleaning and demoulding: Clean the mold with acetone, dry it at 60°C for 24 hours, and evenly apply a layer of polyethylene wax release agent on the dry mold surface; S2. Laying fiberglass mesh cloth and closing the mold: Lay the fiberglass mesh in the mold, roll it to remove air bubbles, and then put the mold together to ensure that all edges and gaps fit tightly; S3, mold preheating: After checking the air tightness, preheat the mold and keep it at 80℃ for 1h; S4. Rubber preparation: The epoxy resin was preheated at 80°C for 30 minutes, and then the epoxy resin: curing agent: flame retardant powder: filler with a mass ratio of 25:25:28:15 was stirred at a speed of 1000 r / min in a stirring kettle for 30 minutes, and a rubber compound was prepared by vacuum degassing. S5. Vacuum casting: The vacuum degree in the mold is drawn to -0.85MPa, and then the rubber material is introduced into the mold from the bottom, and poured from bottom to top until the rubber material fills the top outlet of the mold, and then the valve at the top outlet of the mold is closed, and the pressure of the mold filled with rubber material is increased to 0.6MPa at a pressure increase rate of 0.1MPa / min, where the valve is closed for 2min, opened for 30s, and the pressure is maintained for 10min; S6, curing and demoulding: The mold after step S5 is cured at high temperature, first the temperature is raised to 100°C and kept for 2 hours, then raised to 125°C and kept for 4 hours, and after complete curing, it is naturally cooled to room temperature, demoulding, and CNC trimming are performed to obtain the FRP cylinder A; S7, post-processing: The surface of the FRP cylinder A after step S6 is subjected to sandblasting and epoxy resin paint spraying treatment to obtain the FRP cylinder. The sand used in the sandblasting treatment is quartz sand material with a particle size of 100 meshes and a treatment pressure of 5.0 MPa.

[0033] Example 2 Preparation of filler: S2.1, quartz powder and aluminate coupling agent in a mass ratio of 30:1 were mixed, ball milled at a speed of 300 r / min for 3 h, and then passed through a 200 mesh sieve to obtain a mixture A, and then anhydrous ethanol 7 times the mass of the mixture A was added, stirred at a speed of 500 r / min for 1.5 h at 43°C, heated to 110°C, and dried for 12 h to obtain a mixture B; S2.2. A mixture of B, polyacrylamide and deionized water in a mass ratio of 10:1:25 was stirred at a constant speed for 1.5 h, and dried at 90°C for 12 h to obtain solid C. Solid C was ground at a speed of 300 r / min for 3 h and then passed through a 300-mesh sieve to obtain modified quartz powder.

[0034] Preparation of flame retardant powder: S3.1, in parts by weight, at room temperature, 13 parts of barium carbonate are dispersed in 80 parts of deionized water to obtain a suspension A, and 13 parts of phytic acid are dissolved in 65 parts of deionized water to obtain a phytic acid solution, the phytic acid solution and the suspension A are mixed and stirred at a speed of 350 r / min for 5 hours, after the stirring is completed, the mixture is filtered and washed with deionized water for 5 times, and the obtained solid is dried at 77°C for 15 hours to obtain a barium phytate solid; S3.2. Aluminum hydroxide and barium phytate solids in a mass ratio of 4:1 are stirred at a speed of 350 r / min for 25 minutes to obtain a mixture C. 20 parts of the mixture C are mixed with 23 parts of a lignin mixed liquid, wherein the lignin mixed liquid contains nano-lignin, ethanol and water in a mass ratio of 2:2:7. The mixture is stirred at a speed of 350 r / min for 3 hours, dried at 87°C for 15 hours, and then ball-milled at a speed of 300 r / min for 1 hour in a ball mill to obtain the flame retardant powder.

[0035] Preparation of FRP cylinder: S1. Cleaning and demoulding: Clean the mold with acetone, dry it at 60°C for 24 hours, and evenly apply a layer of polyethylene wax release agent on the surface of the dried mold; S2. Laying fiberglass mesh cloth and closing the mold: Lay the fiberglass mesh in the mold, roll it to remove air bubbles, and then put the mold together to ensure that all edges and gaps fit tightly; S3, mold preheating: After checking the air tightness, preheat the mold and keep it at 90℃ for 1.5h; S4. Rubber preparation: The epoxy resin was preheated at 80° C. for 30 minutes, and then the epoxy resin: curing agent: flame retardant powder: filler with a mass ratio of 27.5:27.5:30:15 was stirred in a stirring kettle at a speed of 1000 r / min for 40 minutes, and a rubber compound was prepared by vacuum degassing. S5. Vacuum casting: The vacuum degree in the mold is drawn to -0.9MPa, and then the rubber material is introduced into the mold from the bottom, and poured from bottom to top until the rubber material fills the top outlet of the mold, and then the valve at the top outlet of the mold is closed, and the pressure of the mold filled with rubber material is increased to 0.65MPa at a pressure increase rate of 0.1MPa / min, where the valve is closed for 2min, opened for 30s, and the pressure is maintained for 12min; S6, curing and demoulding: The mold after step S5 is cured at high temperature, first the temperature is raised to 100°C and kept for 2.5 hours, then raised to 125°C and kept for 4.5 hours, and after complete curing, it is naturally cooled to room temperature, demoulded, and CNC trimmed to obtain the FRP cylinder A; S7, post-processing: The surface of the FRP cylinder A after step S6 is subjected to sandblasting and epoxy resin paint spraying treatment to obtain the FRP cylinder. The sand used in the sandblasting treatment is quartz sand material with a particle size of 100 meshes and a treatment pressure of 5.0 MPa.

[0036] Example 3 Preparation of filler: S2.1, quartz powder and aluminate coupling agent in a mass ratio of 30:1 were mixed, ball milled at a speed of 300 r / min for 3 h, and then passed through a 200 mesh sieve to obtain a mixture A, and then anhydrous ethanol 7 times the mass of the mixture A was added, stirred at a speed of 500 r / min for 2 h at 45 ° C, heated to 120 ° C and dried for 12 h to obtain a mixture B; S2.2. A mixture of B, polyacrylamide and deionized water in a mass ratio of 10:1:25 was stirred at a constant speed for 2 h. After drying at 90°C for 12 h, solid C was obtained. Solid C was ground at a speed of 300 r / min for 3 h and then passed through a 300-mesh sieve to obtain modified quartz powder.

[0037] Preparation of flame retardant powder: S3.1. In parts by weight, at room temperature, 15 parts of barium carbonate are dispersed in 90 parts of deionized water to obtain a suspension A, and 15 parts of phytic acid are dissolved in 65 parts of deionized water to obtain a phytic acid solution. The phytic acid solution and the suspension A are mixed and stirred at a speed of 400 r / min for 5 hours. After the stirring is completed, the mixture is filtered and washed with deionized water for 5 times. The obtained solid is dried at 80° C. for 17 hours to obtain a barium phytate solid. S3.2. Aluminum hydroxide and barium phytate solids in a mass ratio of 5:1 are stirred at a speed of 400 r / min for 30 minutes to obtain a mixture C, 20 parts of the mixture C are mixed with 25 parts of a lignin mixed liquid, wherein the lignin mixed liquid contains nano-lignin, ethanol and water in a mass ratio of 2:2:7, stirred at a speed of 400 r / min for 4 hours, dried at 95°C for 15 hours, and then ball-milled at a speed of 300 r / min for 1 hour in a ball mill to obtain the flame retardant powder.

[0038] Preparation of FRP cylinder: S1. Cleaning and demoulding: Clean the mold with acetone, dry it at 60°C for 24 hours, and evenly apply a layer of polyethylene wax release agent on the dry mold surface; S2. Laying fiberglass mesh cloth and closing the mold: Lay the fiberglass mesh in the mold, roll it to remove air bubbles, and then put the mold together to ensure that all edges and gaps fit tightly; S3, mold preheating: After checking the air tightness, preheat the mold and keep it at 100℃ for 2h; S4. Rubber preparation: The epoxy resin was preheated at 80° C. for 30 minutes, and then the epoxy resin: curing agent: flame retardant powder: filler with a mass ratio of 30:30:32:15 was stirred in a stirring kettle at a speed of 1000 r / min for 50 minutes, and a rubber compound was prepared by vacuum degassing. S5. Vacuum casting: The vacuum degree in the mold is drawn to -0.95MPa, and then the rubber material is introduced into the mold from the bottom, and poured from bottom to top until the rubber material fills the top outlet of the mold, and then the valve at the top outlet of the mold is closed, and the pressure of the mold filled with rubber material is increased to 0.7MPa at a pressure increase rate of 0.1MPa / min, where the valve is closed for 2min, opened for 30s, and the pressure is maintained for 15min; S6, curing and demoulding: The mold after step S5 is cured at high temperature, first the temperature is raised to 100°C and kept for 3 hours, then raised to 125°C and kept for 5 hours, and after complete curing, it is naturally cooled to room temperature, demoulded, and CNC trimmed to obtain the FRP cylinder A; S7, post-processing: The surface of the FRP cylinder A after step S6 is subjected to sandblasting and epoxy resin paint spraying treatment to obtain the FRP cylinder. The sand used in the sandblasting treatment is quartz sand material with a particle size of 100 meshes and a treatment pressure of 5.0 MPa.

[0039] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the quartz is not modified during the preparation of the filler in Comparative Example 1, and the other operations are the same.

[0040] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that barium phytate is not added during the preparation of the flame retardant powder in Comparative Example 2, and the other operations are the same.

[0041] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that no lignin is added during the preparation of the flame retardant powder in Comparative Example 3, and the other operations are the same.

[0042] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that in Comparative Example 4, the flame retardant powder is only aluminum hydroxide, and the other operations are the same.

[0043] Comparative Example 5 The difference between Comparative Example 5 and Example 1 is that in Comparative Example 5, vacuum casting is performed according to the conventional process: the vacuum degree in the mold is drawn to -0.85 MPa, and then the rubber material is passed into the mold from top to bottom, and after the mold is filled with the rubber material, the mold pressure is increased to 0.6 MPa and the pressure is maintained for 10 minutes; Performance Test: 1. Flame retardant performance: refer to UL-94 "Standard for Flame Test of Plastic Materials for Equipment and Appliance Components", the results are as follows in Table 1: Table 1

[0044] 2. Axial bending strength: refer to GB / T 1449-2005, axial tensile strength and elastic modulus: refer to GB / T1447-2005, dielectric strength: refer to GB / T 1408.1-2016, dielectric parameters: refer to GB / T 1410-2006, the test results are shown in Table 2 below: Table 2

[0045] According to the above data, it can be seen that the glass fiber reinforced plastic cylinder prepared by the present invention has good flame retardancy and mechanical properties.

[0046] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A process for manufacturing a glass fiber reinforced plastic cylinder, characterized in that: The following steps are involved: S1. Cleaning and demoulding: Clean the mold with acetone, dry it at 60°C for 24 hours, and evenly apply a layer of polyethylene wax release agent on the dry mold surface; S2. Laying fiberglass mesh cloth and closing the mold: Lay the fiberglass mesh in the mold, roll it to remove air bubbles, and then put the mold together to ensure that all edges and gaps fit tightly; S3, mold preheating: After checking the air tightness, preheat the mold and keep it at 80~100℃ for 1~2h; S4. Rubber preparation: The epoxy resin was preheated at 80°C for 30 minutes, and then the epoxy resin: curing agent: flame retardant powder: filler with a mass ratio of (25-30): (25-30): (28-32): 15 was stirred in a stirring kettle at a speed of 1000 r / min for 30-50 minutes, and a rubber compound was prepared by vacuum degassing. S5. Vacuum casting: The vacuum degree in the mold is drawn to -0.85~-0.95MPa, and then the rubber material is introduced into the mold from the bottom, and poured from bottom to top until the rubber material fills the top outlet of the mold, and then the valve at the top outlet of the mold is closed, and the pressure of the mold filled with rubber material is increased to 0.6~0.7MPa, and the pressure increase rate is 0.1MPa / min, in which the valve is closed for 2min, opened for 30s, and the pressure is maintained for 10~15min; S6, curing and demoulding: The mold after step S5 is cured at high temperature, and after being completely cured, it is naturally cooled to room temperature, demoulding, and CNC trimming are performed to obtain the FRP cylinder A; S7, post-processing: The surface of the FRP cylinder A after step S6 is subjected to sandblasting and paint spraying treatment to obtain the FRP cylinder.

2. The manufacturing process of the glass fiber reinforced plastic cylinder according to claim 1 is characterized in that: In step S4, the preparation process of the filler is as follows: S2.1, quartz powder and aluminate coupling agent in a mass ratio of 30:1 were mixed, ball milled at a speed of 300 r / min for 3 h, and then passed through a 200 mesh sieve to obtain a mixture A, and then anhydrous ethanol 7 times the mass of the mixture A was added, stirred at a speed of 500 r / min for 1-2 h at 40-45 ° C, heated to 100-120 ° C, and dried for 12 h to obtain a mixture B; S2.

2. A mixture of B, polyacrylamide and deionized water in a mass ratio of 10:1:25 is stirred at a constant speed for 1-2 hours to obtain a solid C after drying. The solid C is ground at a speed of 300 r / min for 3 hours and then passed through a 300-mesh sieve to obtain modified quartz powder.

3. The manufacturing process of the glass fiber reinforced plastic cylinder according to claim 1 is characterized in that: In step S4, the preparation process of the flame retardant powder is as follows: S3.1, in parts by weight, at room temperature, 10 to 15 parts of barium carbonate are dispersed in 70 to 90 parts of deionized water to obtain a suspension A, and 10 to 15 parts of phytic acid are dissolved in 65 parts of deionized water to obtain a phytic acid solution, the phytic acid solution and the suspension A are mixed and stirred at a speed of 300 to 400 r / min for 5 hours, and after the stirring is completed, the mixture is filtered, washed with deionized water, and the obtained solid is dried to obtain a barium phytate solid; S3.

2. Aluminum hydroxide and barium phytate solids in a mass ratio of (3-5):1 are stirred at a speed of 300-400 r / min for 20-30 min to obtain a mixture C, 20 parts of the mixture C are mixed with 20-25 parts of a lignin mixed solution, stirred at a speed of 300-400 r / min for 2-4 h, dried at 80-95°C for 15 h, and then ball-milled at a speed of 300 r / min for 1 h in a ball mill to obtain the flame retardant powder.

4. The manufacturing process of the glass fiber reinforced plastic cylinder according to claim 1 is characterized in that: In step S2, the glass fiber mesh is a twist-free woven reinforced mesh.

5. The manufacturing process of the glass fiber reinforced plastic cylinder according to claim 1 is characterized in that: In step S6, the process of curing at high temperature is: firstly raising the temperature to 100°C and keeping it for 2-3 hours, and then raising the temperature to 125°C and keeping it for 4-5 hours.

6. The manufacturing process of the glass fiber reinforced plastic cylinder according to claim 1 is characterized in that: In step S7, the sand used in the sand blasting is quartz sand material with a particle size of 100 meshes and a processing pressure of 5.0 MPa.

7. The manufacturing process of the glass fiber reinforced plastic cylinder according to claim 1 is characterized in that: In step S7, the paint is epoxy resin paint.

8. The manufacturing process of the glass fiber reinforced plastic cylinder according to claim 2 is characterized in that: In step S2.2, the drying condition is drying at 90° C. for 12 hours.

9. The manufacturing process of the glass fiber reinforced plastic cylinder according to claim 3 is characterized in that: In step S3.1, the drying condition is drying at 75-80°C for 12-17h.

10. The manufacturing process of the glass fiber reinforced plastic cylinder according to claim 3, characterized in that: In step S3.2, the lignin mixed solution contains nano-lignin, ethanol and water in a mass ratio of 2:2:7.

Citation Information

Patent Citations

  • Production method of flame-retardant high-strength fiberglass-reinforced-plastic grid

    CN103387751A

  • Manufacturing process for glass fiber-reinforced plastic product

    CN108773089A

  • Glass fiber reinforced plastic pouring process

    CN111055511A

  • Manufacturing method of wind power blade

    CN113400670A

  • Injection molding method of carbon fiber / silicon resin composite material

    CN117162383A